(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
In Ayurveda, most of the skin diseases are included under Kushtha. It can be classified into two groups which are Mahakushtha and Kshudrakushtha. Vicharchika is one among the Kshudrakushtha. According to classical texts, it can be characterised by Kandu (itching sensation), Shyava (blackish brown discolouration), Pidaka (eruptions), Bahusrava (excessive exudation), Raji (marked lining/lichenification), Atiruja (excessive pain) and Rukshata (dryness). Vicharchika can be correlated with Lichen Simplex Chronicus (LSC) based on its clinical presentation. LSC is a highly pruritic, circumscribed plaque or plaques of lichenified skin due to chronic scratching or rubbing. Vicharchika can be treated with Nidan parivarjana (Avoidance of etiological factors), Shodhana chikitsa (Purification therapy) and Shamana chikitsa (Palliative therapy). The present case study deals with a 45 years old male patient having complaints of severe itching in the palm of both hands associated with marked lining, dryness and thickened skin at the affected site for 5-6 months. This case is diagnosed as Vicharchika (Lichen Simplex Chronicus). For treatment Shamana chikitsa was administered for 1 month which showed good result.